Nilai Nilai Pendidikan Karakter Siswa Dalam Pembelajaran IPS SDN 25 Kota Ternate - Tawari, Iswan E (Peneliti.net, 2023)
Character education in social studies learning has an important role in shaping positive attitudes and behavior of students. Social studies subjects, which involve social, economic, and political life, provide opportunities for students to learn and apply values such as honesty, responsibility, cooperation, tolerance, and social care. In social studies learning, character education values can be instilled through various interactive learning methods and strategies, such as group discussions, case studies, or the use of relevant media and technology. Social studies learning also helps students understand the relationship between character education values and social and real- life contexts, where they can learn about the application of values such as justice, democracy and human rights in society, the state and international relations. Therefore, social studies learning has an important role in helping students develop critical and analytical thinking. However, collaboration between teachers, students, parents, and the school environment is also needed to create a learning environment that supports the formation of student character.